Complications and management after a nonsurgical rhinoplasty: A literature review. Issue 4 (25th June 2019) - Bertossi, Dario; Giampaoli, Giorgio; Verner, Ines; Pirayesh, Ali; Nocini, Riccardo; Nocini, Pierfrancesco
Abstract: Nonsurgical rhinoplasty with injectable fillers has become an increasingly popular option in recent years. Their rise in popularity has been driven by a number of factors, including their minimally invasive nature and the cost lower than surgical option. Physicians should keep in mind that there are many possible complications, especially in the hands of a novice injector. Fortunately, most complications are minor and transient in nature, although the patient may consider them aesthetically displeasing and unacceptable. Major complications are rare; however, an inadequate treatment can produce transient to permanent damage for the patient. A review of the medical literature from 2002 was performed to gather information on main complications after nasal injections using the databases of the National Library of Medicine, Ovid MEDLINE, and Cochrane Library. Understanding the basic anatomical knowledge of the midface, especially the vascular system, is fundamental to prevent the appearance of complications. However, recognize immediately the symptoms and know the correct treatment in case of complications is the only way to minimize permanent bad outcome.